9. UTILIZATION OF THIRD HARMONIC RATIO STATOR GROUND FAULT PROTECTION AND STATOR GROUND FAULT PROTECTION WITH REDUNDANT 20 HZ VOLTAGE INJECTION FOR RELIABLE STATOR GROUNDING PROTECTION ON GENERATOR NEUTRAL SIDE FOR GROUND CONTROL SYSTEM OPERATION APPLICATION - Muchammad Furqon Muchaddats; Nur Rahma Dona; Ahmad Ilham Kamal; Kurniawan; Budi Sumartono; Dikatama (Jurnal TNI Angkatan Udara, 2025)
This study aims to determine the advantages and disadvantages of using the type of stator grounding fault protection using voltage injection and traditional. As we know there are many types of protection for stator grounding faults on the neutral side of the traditional ones such as neutral overvoltage and using the 3rd harmonic ratio voltage ratio between the generator terminal and the neutral side, this traditional method has some problems in sensitivity, safety and cleaning speed, in the long run can make low-level grounding faults become damaging disturbances. And now we already have the latest method for stator grounding faults, using 20Hz voltage injection which can reduce the problems in the traditional ones. The only problem with 20Hz voltage injection is the voltage injector device, if this device has some problems, then the protection cannot operate. This paper wants to explain the advantages of traditional protection (3rd harmonic ratio stator grounding protection) and stator grounding protection with 20Hz voltage injection installed redundantly, then the stator grounding protection on the neutral side of the generator will be more reliable.